Synthesis and antituberculosis activity of new N-phenyl-N'-[4-(5-alkyl/arylamino-1,3,4-thiadiazole-2-yl)phenyl]thioureas - KARAKUŞ, SEVGİ (My University, 2002)
In this study, eight original N-phenyl-N'-[4-(5-alkyl/arylamino-1,3,4-thiadiazole-2-yl)phenyl]thiourea derivatives were synthesized and tested for antituberculosis activity. Antituberculosis activities of the synthesized compounds were screened in vitro using BACTEC 460 Radiometric System against Mycobacterium tuberculosis H37Rv at 6.25 microg/ml. The highest inhibition observed with the synthesized compounds is 67% for N-phenyl-N'-[4-(5-cyclohexylamino-1,3,4-thiadiazole-2-yl)phenyl]thiourea.
Keywords: Microbial Sensitivity Tests; Antitubercular Agents; Molecular Structure; Drug Resistance, Microbial; Structure-Activity Relationship; Thiourea; Magnetic Resonance Spectroscopy; Mycobacterium tuberculosis